Recombinant factor VIII Fc fusion protein engages monocytes via Fc and FVIII domains to reduce monocyte differentiation into osteoclasts - Duan, Susu; Dang, Yifan; Rajani, Gaurav Manohar; Kis-Toth, Katalin; Salas, Joe (Frontiers in Hematology, 2022)
Efmoroctocog alfa, a recombinant factor VIII Fc fusion protein referred to herein as rFVIIIFc, is an extended half-life factor replacement therapy approved for use in patients with hemophilia A. Previous studies have shown that rFVIIIFc has an immunoregulatory effect on monocyte-derived macrophages. This study provides novel findings and an understanding of how rFVIIIFc modulates monocyte differentiation into osteoclasts. rFVIIIFc was found to engage with Fc-gamma receptors (FcγR) on the monocyte surface, leading to increased inhibitory FcγR signaling in cells. Monocyte differentiation into osteoclasts in vitro was inhibited in a concentration-dependent manner following rFVIIIFc treatment, with the interaction between the Fc domain of rFVIIIFc and FcγRII on monocytes playing a role in this effect. The C1 and C2 domains of rFVIIIFc were also found to play a role in inhibiting osteoclast formation. rFVIIIFc treatment of monocytes skewed their differentiation from osteoclasts into a group of less differentiated monocytes with unique myeloid cell phenotypes. The results of this study suggest that rFVIIIFc has a unique immune-regulatory effect on monocyte differentiation, inhibiting osteoclast formation. We propose a “double touchpoint” model for rFVIIIFc interaction with monocytes, with both the Fc domain and domains of FVIII binding to the monocyte surface. Further study is needed to determine if this immune-regulatory effect has any potential benefit on the bone and joint health of patients with hemophilia A receiving rFVIIIFc.